2021
DOI: 10.1016/j.hrthm.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations regarding cardiac stereotactic body radiotherapy for treatment refractory ventricular tachycardia

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Regarding the radiation dose used for cardiac radioablation, most clinical studies used 25 Gy administrated in a single fraction and some have also tried lower doses (15–20 Gy) [ 39 , 40 ]. As the optimal dose has not been established, systematic reviews were performed and efforts have been made to build an expert consensus for future practice [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the radiation dose used for cardiac radioablation, most clinical studies used 25 Gy administrated in a single fraction and some have also tried lower doses (15–20 Gy) [ 39 , 40 ]. As the optimal dose has not been established, systematic reviews were performed and efforts have been made to build an expert consensus for future practice [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews (28,29) showed that most of the patients treated with STAR had multiple recurrences of VT and one or more previous attempts of CA before treatment. As shown…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews ( 28 , 29 ) showed that most of the patients treated with STAR had multiple recurrences of VT and one or more previous attempts of CA before treatment. As shown in Table 1 , most of case series included patients with severe reduction of left ventricular ejection fraction and with III-IV NYHA class.…”
Section: Discussionmentioning
confidence: 99%
“…Die Behandlungen sollten sich an etablierten und publizierten Standards bzgl. Patientenselektion, Therapie, Nachsorge und Dokumentation orientieren [ 11 , 12 ].…”
Section: Fazitunclassified